2004
DOI: 10.1093/jac/dkh346
|View full text |Cite
|
Sign up to set email alerts
|

Osteomyelitis prevention in rabbits using antimicrobial peptide hLF1-11- or gentamicin-containing calcium phosphate cement

Abstract: Local prophylaxis with hLF1-11 effectively reduced development of osteomyelitis in a rabbit model, but gentamicin resulted in a larger number of sterile femora.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
59
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 29 publications
1
59
0
Order By: Relevance
“…In rabbit model trials using cement containing hLf (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11), two studies [56,57] revealed a significant reduction of bone-injected S. aureus ATCC 10832 bacteria or S. aureus (W234) compared with the control group. The results clearly showed that hLf (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11) has the ability to reduce osteomyelitis, with microbiological results similar to those of gentamicin [57].…”
Section: Main In Vivo Results In Human and Animal Modelsmentioning
confidence: 99%
“…In rabbit model trials using cement containing hLf (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11), two studies [56,57] revealed a significant reduction of bone-injected S. aureus ATCC 10832 bacteria or S. aureus (W234) compared with the control group. The results clearly showed that hLf (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11) has the ability to reduce osteomyelitis, with microbiological results similar to those of gentamicin [57].…”
Section: Main In Vivo Results In Human and Animal Modelsmentioning
confidence: 99%
“…AMPs are also generally able to distinguish between mammalian and bacterial cell membranes due to the predominance of negatively charged lipids on the surface of bacterial membranes not seen with mammalian cells [42]. An example of a naturally occurring antimicrobial peptide is human lactoferrin 1-11 [45]. Synthetic analogues of these naturally-occurring peptides, such as arylamide foldamers, have been synthesized and shown to be effective against bacteria [42,43].…”
Section: Alternatives To Conventional Antibioticsmentioning
confidence: 99%
“…There has been interest in local delivery of AMPs as an alternative to conventional antibiotics. Several studies have described local delivery of AMPs in vitro and in vivo via calcium phosphate carrier [44][45][46]. These studies show that it is possible to incorporate and locally release AMPs while retaining antimicrobial activity, although broad-spectrum AMPs such as human lactoferrin 1-11 may not be as potent as conventional antibiotics such as gentamicin [44][45][46].…”
Section: Alternatives To Conventional Antibioticsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general calcium phosphate bone cements showed a high and prolonged in vitro release of hLF1-11 in its biologically active form (22). Furthermore, we also showed that hLF1-11 incorporated into calcium phosphate bone cement can prevent S. aureus osteomyelitis in rabbits (21). Therefore, the aim of the present investigation was to evaluate and compare the performance of hLF1-11 and gentamicin incorporated into calcium phosphate bone cement to treat MRSA osteomyelitis in rabbits.…”
mentioning
confidence: 90%